2006
DOI: 10.7326/0003-4819-144-7-200604040-00005
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Diabetes Processes of Care and Intermediate Outcomes: United States, 1988–2002

Abstract: Diabetes processes of care and intermediate outcomes have improved nationally in the past decade. But 2 in 5 persons with diabetes still have poor LDL cholesterol control, 1 in 3 persons still has poor blood pressure control, and 1 in 5 persons still has poor glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
335
4
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(365 citation statements)
references
References 37 publications
22
335
4
4
Order By: Relevance
“…[53][54][55] Our observed processes of care were also similar to national norms. A recent study conducted by Tuncelli et al evaluating 5-year trends from 1997 to 2001 found that LDL testing improved from 37% to 67%.…”
Section: Discussionsupporting
confidence: 51%
“…[53][54][55] Our observed processes of care were also similar to national norms. A recent study conducted by Tuncelli et al evaluating 5-year trends from 1997 to 2001 found that LDL testing improved from 37% to 67%.…”
Section: Discussionsupporting
confidence: 51%
“…Patients with other chronic multisystem disorders, e.g., asthma, diabetes mellitus, and congestive heart failure, have benefited from the introduction and implementation of protocols for disease management including definition of quantifiable therapeutic goals [13][14][15][16][17]. For GD1, therapeutic goals believed to be clinically meaningful, but not necessarily equivalent to normal values [18], and monitoring guidelines [11] have been proposed in the context of a disease management algorithm that may be applied to current and future treatments (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a reduction in mortality from cardiovascular disease over the past 30 years in most developed countries [4,5] which can be partly attributed to improved management of risk factors over this period [6,7]. Whilst recent studies from the US have shown reductions in incident cardiovascular disease events among adults with diabetes, these reductions have been much smaller than in people without diabetes [8,9].…”
Section: Introductionmentioning
confidence: 99%